Nilai-Nilai Pendidikan Karakter Dalam Serat Wedhatama Karya Kanjeng Gusti Pangeran Adipati Arya Mangkunegara IV - Aji Ari Wibowo; Hakiman, S.Pd.I., M.Pd. (2025)
The moral and ethical degradation of teenagers is partly influenced by the flow of globalisation in Indonesia. To overcome this, it is necessary to instil character education values, not only through formal education, but also through literary works such as Serat Wedhatama. Unfortunately, this work is not well known among the younger generation due to their low interest in local wisdom and the strong influence of Western culture. This study aims to identify the character education values in Serat Wedhatama by Kanjeng Gusti Pangeran Adipati Arya Mangkunegara IV. The method used is library research with a descriptive qualitative approach. Data was obtained from primary and secondary sources through documentation techniques, while data validity was tested through careful observation. Data analysis was conducted through six stages, starting from unit determination, sample selection, data recording, data simplification, and description of results. The results of the study revealed five character education values, namely religious, honest, tolerant, hardworking, and peace-loving. Religious values teach the four types of worship: physical worship, creative worship, spiritual worship, and emotional worship. Honesty values emphasise speaking the truth and acknowledging one's shortcomings. Tolerance values teach respect for differences. Hard work values encourage constant effort to earn rewards and glory. Peaceful love values teach compromise, forgiveness, and non-retaliation.